Differences in catch-up growth and its relationship to nutritional status between SGA and AGA twins and singletons in the first year after birth: a prospective cohort study - Minghui Xiong; Ting Pan; Zhanzhan Zhang; Yuanfeng Zhong; Qian Chen; Yannan Wan; Lin Zhu; Li Chen; Xuan Zhang (Scientific Reports)
Abstract To compare the difference between appropriate for gestational age (AGA) and small for gestational age (SGA) of singleton and twin in terms of catch-up growth (CUG) and nutritional status in the first year after birth through a prospective cohort study. A total of 340 singleton and twin children were recruited. Dietary questionnaires were completed at enrollment and at 3 and 6 months of age. Anthropometric data were presented as Z scores. The Z score of weight, length and/or head circumference > − 2SD were used as criteria for CUG. The CUG rate of the twin AGA was the highest. Rapid CUG of twin SGA occurred within 3 months, and the CUG rate of weight was greater for twin SGA than for singleton SGA at 1 year old. The length CUG rate for twin SGA was the lowest within 3 months, 17.05% of the singleton SGA and 22.22% of the twin SGA did not reach CUG. The CUG was independent of feeding mode, and higher energy support did not improve CUG outcome. Twin AGA children have a better CUG rate, whereas CUG might take longer in SGA, especially for twin SGA. Higher energy support does not necessarily improve CUG outcomes. Trial registration number The study was registered in the Chinese Clinical Trial Registry with registration number ChiCTR2100053434 and was recorded in the medical research registry. Date of registration: Nov 21, 2021